Microstructure and dielectric properties of CaCu3Ti4O12 ceramic - Mohamed, Julie J.; Hutagalung, Sabar D.; Ain, M. Fadzil; Deraman, Karim; Ahmad, Zainal A. (Elservier, 2007)
CaCu3Ti4O12 (CCTO) was prepared by the solid state technique. The sample was calcined at 900 °C/12 h and sintered at 1050 °C/24 h, then subjected to XRD to ensure CCTO formation. The microstructure was observed by SEM. XRD results identified both samples as single phase CCTO, whereas the microstructure shows abnormal grain growth and large pores. Sintering was studied in the temperature range of 950–1050 °C for 3–12 h. Increasing sintering temperature enhances the density and secondary formation of Cu2O. A clear grain boundary and dense microstructure were observed. The results show that the sample sintered at 1040 °C/10 h yields a clearly uniform grain size with the highest εr (33,210)